Teacher Perceptions of a Culture of Thinking - Gary G. Andersen (The Advocate, 2018)
Building classroom and school cultures of thinking is one of the fundamental and critical purposes of education. This study is an exploratory effort to obtain a clearer picture of teachers’ perceptions about eight components of a culture of thinking within their own classroom. The instrument used is a quantitative survey developed by Ritchhart (2015) that examines eight forces of cultures of thinking (expectations, language, modeling, time, opportunities, routines, physical environment and interactions). The survey results provide useful information about potential target areas for those seeking to deepen cultures of thinking in educational settings.